Computation of AC flashover voltage of polluted HV insulators using a dynamic arc model - Gencoglu, M. T.; Cebeci, M. (Wiley, 2009)
Flashover of polluted insulators is still a serious threat to the safe operation of a power transmission system. Despite the extensive investigations carried out on the pollution performance of the insulators, the flashover characteristics are not well understood. Recent theoretical and experimental research on polluted insulators is yet to yield a perfect generalized mathematical model which can accurately predict critical flashover voltage. In this paper, the pollution flashover on the high voltage insulators has been investigated and a new dynamic arc model has been proposed. For this purpose, firstly the concerned insulators' scaled shapes were partitioned into triangular elements, then finite element method (FEM) was implemented for obtaining potential distribution on the surface of insulator and finally flashover voltages were determined by using the developed arc model. For a number of common insulators of different geometries the computed results of flashover voltages on the selected string insulators have been compared to experimental results of some other research. Pollution flashover behaviors of the insulators have been taken into consideration and the validity of the model was thus verified. Copyright (C) 2008 John Wiley & Sons, Ltd.
Keywords: Pollution flashover; flashover voltage; dynamic arc model